GW274150, a potent and highly selective inhibitor of iNOS, reduces experimental renal ischemia/reperfusion injury - Chatterjee, PK (2015)
Background. Generation of nitric oxide (NO) by inducible nitric oxide synthase (iNOS) may contribute to renal ischemia/reperfusion (I/R) injury. The aim of this study was to investigate the effects of GW274150, a novel, highly selective, potent and long-acting inhibitor of iNOS activity in rat and mouse models of renal I/R. Methods. Rats were administered GW274150 (5 mg/kg intravenous bolus administered 30 minutes prior to I/R) and subjected to bilateral renal ischemia (45 minutes) followed by reperfusion (6 hours). Serum and urinary indicators of renal dysfunction, tubular and reperfusion injury were measured, specifically, serum urea, creatinine, aspartate aminotransferase (AST) and N-acetyl-beta-d-glucosaminidase (NAG) enzymuria. In addition, renal sections were used for histologic scoring of renal injury and for immunologic evidence of nitrotyrosine formation and poly [adenosine diphosphate (ADP)-ribose] (PAR). Nitrate levels were measured in rat plasma using the Griess assay. Mice (wild-type, administered 5 mg/kg GW274150, and iNOS-/-) were subjected to bilateral renal ischemia (30 minutes) followed by reperfusion (24 hours) after which renal dysfunction (serum urea, creatinine), renal myeloperoxidase (MPO) activity and malondialdehyde (MDA) levels were measured. Results. GW274150, administered prior to I/R, significantly reduced serum urea, serum creatinine, AST, and NAG indicating reduction of renal dysfunction and injury caused by I/R. GW274150 reduced histologic evidence of tubular injury and markedly reduced immunohistochemical evidence of nitrotyrosine and PAR formation, indicating reduced peroxynitrite formation and poly (ADP-ribose) polymerase (PARP) activation, respectively. GW274150 abolished the rise in the plasma levels of nitrate (indicating reduced NO production). GW274150 also reduced the renal dysfunction in wild-type mice to levels similar to that observed in iNOS-/- mice subjected to I/R. Renal MPO activity and MDA levels were significantly reduced in wild-type mice administered GW274150 and iNOS-/- mice subjected to renal I/R, indicating reduced polymorphonuclear leukocyte (PMN) infiltration and lipid peroxidation. Conclusions. These results suggest that (1) an enhanced formation of NO by iNOS contributes to the pathophysiology of renal I/R injury and (2) GW274150 reduces I/R injury of the kidney. We propose that selective inhibitors of iNOS activity may be useful against renal dysfunction and injury associated with I/R of the kidney.